RNA splicing: a split consensus reveals two major 5′ splice site classes - Matthew T. Parker; Sebastian M. Fica; Gordon G. Simpson (Open Biology)
The established consensus sequence for human 5′ splice sites masks the presence of two major splice site classes defined by preferential base-pairing potentials with either U5 snRNA loop 1 or the U6 snRNA ACAGA box. The two 5′ splice site classes are separable in genome sequences, sensitized by specific genotypes and associated with splicing complexity. The two classes reflect the commitment to 5′ splice site usage occurring primarily during 5′ splice site transfer to U6 snRNA. Separating the human 5′ splice site consensus into its two major constituents can help us understand fundamental features of eukaryote genome architecture and splicing mechanisms and inform treatment design for diseases caused by genetic variation affecting splicing.